The Legal Impact of Islamic Law in the Identity and Provisions of Qatari Legal System: Conceptual Frame and Legislative Directions - Abdullah Abdullah (Al-Jami'ah Research Centre, 2020)
This article examines the Islamic law situation in Qatari law based on a case study to the main concepts, and some special practical issues in Qatari Law. The paper focuses on a conceptual approach to Qatari law and Islamic law in the light of centrality of Islamic law. Furthermore this paper also focuses on the distinctive characteristics of the law compared to the other such as the concept of human behavior in such a way that it has an impact on the penalty in the legal rule as a distinct component. The analysis also pays an attention to a distinction between the legal rules and other social rules in the matter of giving an influence on structure of human behavior. As a matter of fact, this article also tries to give e light on the centrality of Islamic law on Qatari law, especially on the case of taking back of charity (hibah) as an example. The paper ends with conclusion that for Islamic legislation in Qatari law, Islamic Sharia is considered to be the main source and it is needed to develop a legislative and judicial orientations based on Islamic legal rules that regulate transactions in Qatari law.[Artikel ini membahas situasi hukum Islam di dalam hukum Negara Qatar berdasarkan pada studi kasus atas beberapa konsep kunci dan isu praktis dalam hukum Qatar. Tulisan ini fokus pada pendekatan konseptual hukum Qatar dan Syariah Islam berdasarkan pada sentralitas Syari’ah islam. Selain itu, artikel ini juga membahas tentang karakter khusus undang-undang dibanding dengan yang lainnya seperti teori prilaku yang mempunyai pengaruh terhadap penerapan hukumannya. Selain itu, pembahasan tersebut juga mempertimbangkan perbedaannya dibandingkan dengan hukum sosial terkait dengan pengaruh terhadap pembentukan prilaku. Artikel ini juga memberikan penekanan kajian atas sentralitas hukum Islam dan pengaruhnya terhadap konsep undang-undang seperti pengaturan tentang hak menarik kembali dana hibah dalam undang-undang di Qatar. Dalam kesimpulan, artikel ini menyatakan bahwa dalam undang-undang Qatar, hukum Islam menempati posisi yang sentral dan menjadi basis utama dalam pengembangan legislatif dan orientasi yuridis yang didasarkan pada aturan legal Islam dalam pengaturan transaksi dalam undang-undang hukum di Qatar.]